BEYOND THE HEADLINES: MEDIA DEPENDENCY AND SOCIAL MEDIA NEWS CONSUMPTION AMONG YOUTH - Sachu, Berlin; K B Sankaranaraynan; Kadeswaran S (International Journal of Research -GRANTHAALAYAH, 2025)
In this digital age, social media platforms have emerged as a dominant source of news, particularly among youngsters. This study explores the perception and usage of social media as a source of news among the college students in Coimbatore, Tamilnadu, India. Quantitative research is designed using the framework of Media Dependency Theory (MDT), and data was collected through a structured survey. 192 respondents (83 females, 109 males) were selected using convenience sampling. The study investigated the relationship between demographic factors (age, gender, education), trust in social media news, frequency of news access, device/platform preference, and behavioral engagement. Data was analyzed using SPSS, including descriptive statistics, cross-tabulations, and chi-square tests. Results showed that younger users (below 24) were significantly more likely to trust and depend on social media for news. Males and undergraduates demonstrated higher platform usage and engagement. The findings support the propositions of Media Dependency Theory, highlighting how frequent use, trust, and platform integration into daily routines contribute to cognitive and behavioral media dependency. The study concludes by finding that while social media is a convenient and habitual news source for youth, its influence on perceptions and behavior raises important questions about media trust and the need of digital literacy.